2021
DOI: 10.7759/cureus.13093
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-Induced Leukoencephalopathy

Abstract: Heroin-induced leukoencephalopathy (HLE) is a rare but potentially debilitating and sometimes fatal neurological disorder. Despite the widely practiced heroin use via different routes and modalities, the syndrome is said to be rare and mostly associated with inhaling rather than injecting or snorting practices. We reviewed the literature to address the latest diagnostic, therapeutic, and prognostic measures related to the condition. Here, we present a case of a 35-year-old male who admitted to inhaling heroin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Increased white matter lactate and response to antioxidants indicate that HIL may be related to a mitochondrial dysfunction causing demyelination and oligodendrocyte apoptosis [ 17 ]. Other recently published studies have demonstrated the use and success of antioxidants in the treatment of HIL [ 2 ]. While there is currently no treatment regimen for HIL, antioxidants such as vitamin A, C, E, zinc, coenzyme q10, and selenium are usually recommended [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased white matter lactate and response to antioxidants indicate that HIL may be related to a mitochondrial dysfunction causing demyelination and oligodendrocyte apoptosis [ 17 ]. Other recently published studies have demonstrated the use and success of antioxidants in the treatment of HIL [ 2 ]. While there is currently no treatment regimen for HIL, antioxidants such as vitamin A, C, E, zinc, coenzyme q10, and selenium are usually recommended [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIL is a rare neurologic disorder associated with inhaling heroin vapors. The pathophysiology is poorly understood at this time, but the condition appears to affect mainly white matter in the brain, differentiating from other types of leukoencephalopathies [ 2 ]. Fluid accumulates within the myelin sheath causing a spongiform myelinopathy, vacuolar degeneration, and demyelination that is visible on magnetic resonance imaging (MRI) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of reversal with naloxone in the setting of acute opioid overdose and removal of exposure to the offending agent, treatment is supportive. Prognostication is difficult because wide-ranging outcomes have been observed, including full recovery, survival with long-term disability, and death 24 …”
Section: Opioidsmentioning
confidence: 99%
“…Prognostication is difficult because wide-ranging outcomes have been observed, including full recovery, survival with long-term disability, and death. 24 While the brain is at risk for serious insult associated with opioids, the spinal cord and even the peripheral nervous system are potential targets as well. Various presentations of myelopathy are associated with heroin exposure, 25 including acute paraparesis in the setting of heroin insufflation with features suggestive of spinal cord ischemia such as selective anterior horn cell T2 hyperintensity on MRI.…”
Section: Key Pointsmentioning
confidence: 99%
“…Die Heroin-induzierte spongiforme Leukenzephalopathie ist oft rasch progredient und führt unbehandelt in 23 % der Fälle zum Tod [17]. Wenn sie reichtzeitig erkannt wird, besteht die Behandlung in der hochdosierten Gabe von Coenzym-Q10, Vitamin-E und Vitamin-C [18]. hunderts verwendete Methamphetamin ("Crystal Meth") sowie MDMA (3,4-Methylendioxy-N-methylamphetamin, "Speed").…”
Section: Caveunclassified